GENERATIVE DESIGN OF STRUCTURAL STEEL JOINTS (Advances in Civil and Architectural Engineering, 2022)
Structural project is based on technical regulations, structural codes, construction conditions, and client requirements. Through the structural design process, some important decisions that can significantly affect the final result must be implemented. The most important factor for optimal design is the reduction in material and overall work costs. Selecting appropriate joint configurations that can reduce the overall weight and work on the structure is critical. To examine a significant number of possible configurations and their effect on structural behavior, the generative design method (GDM) is used. In this study, software is custom developed, and a relevant example of generative joint structural design is provided. The methodology for the optimal joint and structure design is described comprehensively. The final results show that the GDM is an effective methodology for application in the design of steel structures.